Microstructural and metabolic changes in the longitudinal progression of white matter hyperintensities. Issue 8 (August 2019) - Jiaerken, Yeerfan; Luo, Xiao; Yu, Xinfeng; Huang, Peiyu; Xu, Xiaojun; Zhang, Minming; ,
Our purpose is to evaluate the microstructural and metabolism property in the white matter that later become white matter hyperintensity (WMH), and of WMH that later disappeared. Forty subjects with two-year follow-up were included. Each subject had 3DT1, T2FLAIR, DTI and FDG-PET scans. White matter was classified into: constant WMH, growing WMH, shrinking WMH and normal appearing white matter (NAWM). The average DTI (FA and MD) and FDG-PET (standardized FDG-PET rSUV) of each of the above-mentioned region were extracted and compared. At baseline, the growing WMH had lower FA and FDG-PET rSUV than NAWM, but had higher FA than the constant WMH. Longitudinally, in NAWM, there was a more rapid decline in metabolism compared to WMH areas, while in the growing WMH, a progression in diffusion was found. Finally, we discovered that the shrinking WMH had a similar microstructural and metabolism property and progression to the constant WMH. Our results suggest there are dynamic changes in microstructural and metabolism in WMH. The metabolic change was mainly found in NAWM, while the microstructural change was mainly found in WMH region. Besides, the reduced volume in WMH, to a larger extent, is irrelevant to the microstructural or metabolism recovery.